A high-density low-porosity graphite anode prepared by double-dipping and triple-calcination
Patent Information
- Application Number
- CN202611387655.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]为了克服上述的技术问题,本发明的目的在于提供一种基于二浸三焙制备的高致密低孔隙率石墨匣钵,解决了现有的石墨匣钵的密度低、开口孔隙率高,易于遭受侵蚀,使用寿命短,并且其抗折强度低,易于发生损坏的问题
一种基于二浸三焙制备的高致密低孔隙率石墨匣钵,在制备过程中首先将耐热性酚醛树脂、氧氯化锆、硅烷偶联剂KH-560、去离子水以及乙醇混合均匀,得到粘结料,之后将石墨粉、石墨烯、氧化铝、氧化钇以及粘结料混合均匀,之后倒入至模具中进行压制,得到匣钵生坯,最后将匣钵生坯经过二浸三焙工艺,得到高致密低孔隙率石墨匣钵;该石墨匣钵使用耐热性酚醛树脂作为粘结物质,利用改性液态酚醛树脂作为浸渍物质,使用二浸三焙工艺能够显著提升石墨匣钵的密度和抗折强度,显著降低石墨匣钵的开口气孔率,能够有效阻挡烧结锂电材料过程中氧气和酸性挥发物对石墨匣钵的侵蚀,使匣钵抗氧化性能、耐酸腐蚀性能得以提升,延长了石墨匣钵的使用寿命。
Smart Images

Figure CN122878141A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of graphite saggers, specifically to a high-density, low-porosity graphite sagger prepared by two-dip and three-baking processes. Background Technology
[0002] In the high-temperature sintering process of lithium-ion battery cathode materials (such as ternary materials and lithium iron phosphate), the graphite sagger, as a supporting container, directly affects the quality of the battery material and the production cost. Currently, the industry generally uses pressing molding followed by a single firing to prepare the graphite sagger. This traditional process has significant drawbacks: the prepared graphite sagger has low density and high porosity. In high-temperature, oxygen-rich, or corrosive gas environments, oxygen and corrosive gases can easily penetrate into the sagger through the interconnected pores, leading to oxidation, corrosion, and flaking of the graphite skeleton, resulting in a short service life. Furthermore, the flaked carbon powder can easily contaminate the cathode material and also leads to low flexural strength, making it prone to breakage or deformation during high-speed transport and stacking in automated production lines.
[0003] Therefore, developing a high-density, low-porosity graphite sagger based on a two-dip, three-baking process is of significant practical importance. To address the aforementioned technical shortcomings, a solution is proposed. Summary of the Invention
[0004] In order to overcome the above-mentioned technical problems, the present invention aims to provide a high-density, low-porosity graphite sagger based on a two-dip, three-baking process, which solves the problems of existing graphite saggers having low density, high open porosity, susceptibility to corrosion, short service life, low flexural strength, and easy damage.
[0005] The objective of this invention can be achieved through the following technical solutions: In a first aspect, this application provides a high-density, low-porosity graphite sagger prepared by two-dip and three-baking processes, comprising the following components by weight: The composition includes 70-75 parts graphite powder, 2-6 parts graphene, 3-6 parts heat-resistant phenolic resin, 0.3-0.5 parts zirconium oxychloride, 0.8-1.2 parts alumina, 1-3 parts yttrium oxide, 0.3-0.5 parts silane coupling agent KH-560, 1-3 parts deionized water, and 8-10 parts ethanol. The heat-resistant phenolic resin is prepared by the following steps: Phenol, ammonia solution, and formaldehyde solution were added to a three-necked flask equipped with a stirrer, thermometer, reflux condenser, and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred for 20-30 minutes at a temperature of 20-25℃ and a stirring rate of 300-400 r / min. The temperature was then raised to 70-75℃ and the stirring was continued for 2-3 hours. The mixture was then dehydrated under reduced pressure at a vacuum of -0.08 MPa for 30-40 minutes. Boric acid was then added, and the temperature was raised to 98-100℃ and the stirring was continued for 1-2 hours. The mixture was then dehydrated under reduced pressure at a vacuum of -0.08 MPa for 30-40 minutes. Methyltrimethoxysilane was then added and the mixture was stirred for 30-50 minutes. After the reaction was completed, the product was cooled to room temperature and then placed in a vacuum drying oven at a temperature of 80-90℃ for 2-3 hours to obtain heat-resistant phenolic resin.
[0006] In a preferred embodiment of the present invention, the ratio of phenol, ammonia solution, formaldehyde solution, boric acid and methyltrimethoxysilane is 0.5mol: 6-6.5mL: 65-70g: 0.06-0.08mol: 0.03-0.05mol.
[0007] In a preferred embodiment of the present invention, the ammonia solution has a mass fraction of 27-28%; and the formaldehyde solution has a mass fraction of 37-38%.
[0008] In a preferred embodiment of the present invention, the high-density, low-porosity graphite sagger prepared based on two-dip-three-baking method is prepared by the following steps: Step 1: Weigh out 70-75 parts graphite powder, 2-6 parts graphene, 3-6 parts heat-resistant phenolic resin, 0.3-0.5 parts zirconium oxychloride, 0.8-1.2 parts alumina, 1-3 parts yttrium oxide, 0.3-0.5 parts silane coupling agent KH-560, 1-3 parts deionized water, and 8-10 parts ethanol according to the following proportions by weight, and set aside. Step 2: Mix heat-resistant phenolic resin, zirconium oxychloride, silane coupling agent KH-560, deionized water and ethanol evenly to obtain the binder; Step 3: Mix graphite powder, graphene, alumina, yttrium oxide and binder evenly, then pour into a mold and press for 1-2 hours under a pressure of 8-10 MPa, then press for 40-60 minutes under a pressure of 20-25 MPa, and then press for 1-2 minutes under a pressure of 40-50 MPa to obtain the sagger green blank. Step 4: The green sagger blank is subjected to a two-dip and three-baking process to obtain a high-density, low-porosity graphite sagger.
[0009] In a preferred embodiment of the present invention, the graphite powder is Naio Nano NO-E-002-3 graphite powder.
[0010] In a preferred embodiment of the present invention, the graphene is high-purity graphene from Zhongke Leiming.
[0011] In a preferred embodiment of the present invention, the alumina is α-Al2O3 with an average particle size of 30 nm.
[0012] In a preferred embodiment of the present invention, the average particle size of the yttrium oxide is 50 nm.
[0013] In a preferred embodiment of the present invention, the two-dip three-baking process includes the following steps: Step A1: Place the sagger blank in a high-temperature vacuum furnace for a first sintering to obtain a baked sagger; Step A2: Dip a baking sagger once to obtain a dipped sagger; Step A3: Place the first dipped sagger in a high-temperature vacuum furnace for secondary sintering to obtain a second-baked sagger; Step A4: Dip the two-baking saggers a second time to obtain two-dipping saggers; Step A5: Place the double-dipping sagger in a high-temperature vacuum furnace for three sintering processes to obtain a high-density, low-porosity graphite sagger.
[0014] In a preferred embodiment of the present invention, the conditions for the first sintering in step A1 are: sintering at a temperature of 900-1000℃ for 84-92 hours.
[0015] In a preferred embodiment of the present invention, the conditions for the secondary sintering in step A3 are: sintering at a temperature of 1100-1200℃ for 72-84 hours.
[0016] In a preferred embodiment of the present invention, the conditions for the three sinterings in step A5 are: sintering at a temperature of 1300-1400℃ for 48-60 hours.
[0017] In a preferred embodiment of the present invention, the specific process of the first impregnation in step A2 is as follows: A baking sagger is placed in a high-temperature pressure vessel, preheated to 180-200℃, and then vacuumed to -0.05MPa for 4-6 hours. Modified liquid phenolic resin is then added to submerge the baking sagger, followed by nitrogen gas to pressurize to 4-5MPa. The sagger is then immersed at 180-200℃ for 4-6 hours, and then removed and drained to obtain an immersed sagger.
[0018] In a preferred embodiment of the present invention, the specific process of the secondary impregnation in step A4 is as follows: The double-baked crucible is placed in a high-temperature pressure vessel, preheated to 220-250℃, and then vacuumed to -0.09MPa for 2-3 hours. After that, modified liquid phenolic resin is added to submerge the double-baked crucible, and then nitrogen gas is introduced to pressurize it to 6-8MPa. After that, it is immersed at a temperature of 220-250℃ for 4-6 hours. After that, it is taken out and drained to obtain the double-immersion crucible.
[0019] In a preferred embodiment of the present invention, the modified liquid phenolic resin is PFX003.
[0020] Compared with the prior art, the beneficial effects of the present invention are: A high-density, low-porosity graphite squash prepared using a two-dip, three-baking process is disclosed. The process involves first uniformly mixing heat-resistant phenolic resin, zirconium oxychloride, silane coupling agent KH-560, deionized water, and ethanol to obtain a binder. Then, graphite powder, graphene, alumina, yttrium oxide, and the binder are mixed uniformly and poured into a mold for pressing to obtain a squash green. Finally, the green squash undergoes a two-dip, three-baking process to obtain a high-density, low-porosity graphite squash. This graphite squash uses heat-resistant phenolic resin as the binder and modified liquid phenolic resin as the impregnating agent. The two-dip, three-baking process significantly improves the density and flexural strength of the graphite squash, significantly reduces the open porosity, and effectively prevents the erosion of the graphite squash by oxygen and acidic volatiles during the sintering of lithium battery materials. This enhances the squash's oxidation resistance and acid corrosion resistance, extending its service life.
[0021] In this process, the graphite crucible is repeatedly impregnated with modified liquid phenolic resin. The modified liquid phenolic resin penetrates into the tiny pores inside the graphite crucible and is then carbonized at high temperature to become solid carbon, thereby filling the pores and increasing the density. Pores are channels for oxygen and corrosive gases to enter the material. The two impregnations and three bakings seal these channels, making it difficult for external media to corrode the interior, thus improving the chemical stability of the material in high-temperature environments. The increase in density directly leads to an increase in strength, making it more resistant to external impacts and wear, and making it less prone to cracking and flaking during use, resulting in a longer service life.
[0022] In the preparation of graphite crucibles, a heat-resistant phenolic resin was first prepared. Phenolic resin was prepared using phenol and formaldehyde, and boric acid and methyltrimethoxysilane were used in the reaction to introduce boron and silicon atoms into the molecular chain of the phenolic resin, thus obtaining heat-resistant phenolic resin. The introduction of boron and silicon atoms can effectively improve the heat resistance of phenolic resin by forming chemical bonds with high bond energy, thereby improving the stability of the binder material during the sintering and molding of the graphite crucible, avoiding the formation of a large number of pores inside the graphite crucible, thus significantly reducing internal defects, greatly increasing the density and flexural strength of the graphite crucible, and significantly reducing the open porosity of the graphite crucible. Attached Figure Description
[0023] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to the accompanying drawings.
[0024] Figure 1 This is a surface SEM image of the high-density, low-porosity graphite sagger of Embodiment 3 of the present invention; Figure 2 This is an internal SEM image of the high-density, low-porosity graphite sagger of Embodiment 3 of the present invention; Figure 3 This is a surface SEM image of the high-density, low-porosity graphite sagger of Comparative Example 1 of the present invention. Figure 4 This is an internal SEM image of the high-density, low-porosity graphite sagger of Comparative Example 1 of the present invention. Detailed Implementation
[0025] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] Example 1: This embodiment describes a method for preparing a high-density, low-porosity graphite sagger based on a two-dip, three-baking process, comprising the following steps: Step S1: Add 0.5 mol phenol, 6 mL of 27% ammonia solution and 65 g of 37% formaldehyde solution to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection. Stir and react for 20 min at 20℃ and 300 r / min. Then raise the temperature to 70℃ and continue stirring for 2 h. Then dehydrate under reduced pressure for 30 min at -0.08 MPa. Add 0.06 mol boric acid and raise the temperature to 98℃ and continue stirring for 1 h. Then dehydrate under reduced pressure for 30 min at -0.08 MPa. Then add 0.03 mol methyltrimethoxysilane and continue stirring for 30 min. After the reaction is complete, cool the reaction product to room temperature and then place it in a vacuum drying oven and dry at 80℃ for 2 h to obtain heat-resistant phenolic resin. Step S2: Weigh out 70 parts by weight of graphite powder, 2 parts by weight of graphene, 3 parts by weight of heat-resistant phenolic resin, 0.3 parts by weight of zirconium oxychloride, 0.8 parts by weight of alumina, 1 part by weight of yttrium oxide, 0.3 parts by weight of silane coupling agent KH-560, 1 part by weight of deionized water, and 8 parts by weight of ethanol for later use; the graphite powder is Naio Nano NO-E-002-3 graphite powder; the graphene is Zhongke Leiming high-purity graphene; the alumina is α-Al2O3 with an average particle size of 30 nm; and the yttrium oxide has an average particle size of 50 nm. Step S3: Mix heat-resistant phenolic resin, zirconium oxychloride, silane coupling agent KH-560, deionized water and ethanol evenly to obtain a binder; Step S4: Mix graphite powder, graphene, alumina, yttrium oxide and binder evenly, then pour into a mold and press for 1 hour under a pressure of 8 MPa, then press for 40 minutes under a pressure of 20 MPa, and then press for 1 minute under a pressure of 40 MPa to obtain a sagger green. Step S5: Place the sagger blank in a high-temperature vacuum furnace and sinter it at 900℃ for 84 hours to obtain a sagger. Step S6: Place a baking sagger in a high-temperature pressure vessel, preheat it to 180°C, and then maintain it under vacuum at -0.05MPa for 4 hours. Then, add modified liquid phenolic resin PFX003 to submerge the baking sagger, then introduce nitrogen gas to pressurize it to 4MPa, and then impregnate it at a temperature of 180°C for 4 hours. After that, take it out and drain it to obtain an impregnated sagger. Step S7: Place the first dipped sagger in a high-temperature vacuum furnace and sinter it at 1100℃ for 72 hours to obtain the second dipped sagger. Step S8: Place the double-baked crucible in a high-temperature pressure vessel, preheat it to 220°C, and then maintain it under vacuum at -0.09MPa for 2 hours. Then, add modified liquid phenolic resin PFX003 to submerge the double-baked crucible, then introduce nitrogen gas to pressurize it to 6MPa, and then impregnate it at 220°C for 4 hours. After that, take it out and drain it to obtain the double-impregnated crucible. Step S9: Place the double-dipping sagger in a high-temperature vacuum furnace and sinter it at 1300℃ for 48 hours to obtain a high-density, low-porosity graphite sagger.
[0027] Example 2: This embodiment describes a method for preparing a high-density, low-porosity graphite sagger based on a two-dip, three-baking process, comprising the following steps: Step S1: 0.5 mol phenol, 6.3 mL of 27.5% ammonia solution and 68 g of 37.5% formaldehyde solution were added to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Nitrogen gas was introduced for protection. The mixture was stirred at 22℃ and 350 r / min for 25 min. Then the temperature was raised to 72℃ and the mixture was stirred for 2.5 h. The mixture was then dehydrated under reduced pressure at -0.08 MPa for 35 min. 0.07 mol boric acid was added and the temperature was raised to 99℃ and the mixture was stirred for 1.5 h. The mixture was then dehydrated under reduced pressure at -0.08 MPa for 35 min. 0.04 mol methyltrimethoxysilane was added and the mixture was stirred for 40 min. After the reaction was completed, the reaction product was cooled to room temperature and then placed in a vacuum drying oven and dried at 85℃ for 2.5 h to obtain heat-resistant phenolic resin. Step S2: Weigh out 72 parts by weight of graphite powder, 4 parts by weight of graphene, 4.5 parts by weight of heat-resistant phenolic resin, 0.4 parts by weight of zirconium oxychloride, 1.0 part by weight of alumina, 2 parts by weight of yttrium oxide, 0.4 parts by weight of silane coupling agent KH-560, 2 parts by weight of deionized water, and 9 parts by weight of ethanol for later use; the graphite powder is Naio Nano NO-E-002-3 graphite powder; the graphene is Zhongke Leiming high-purity graphene; the alumina is α-Al2O3 with an average particle size of 30 nm; and the yttrium oxide has an average particle size of 50 nm. Step S3: Mix heat-resistant phenolic resin, zirconium oxychloride, silane coupling agent KH-560, deionized water and ethanol evenly to obtain a binder; Step S4: Mix graphite powder, graphene, alumina, yttrium oxide and binder evenly, then pour into a mold and press for 1.5 hours under a pressure of 9 MPa, then press for 50 minutes under a pressure of 22 MPa, and then press for 1.5 minutes under a pressure of 45 MPa to obtain a sagger green. Step S5: Place the sagger green in a high-temperature vacuum furnace and sinter at 950℃ for 892 hours to obtain a baked sagger. Step S6: Place a baking sagger in a high-temperature pressure vessel, preheat it to 190°C, and then maintain it under vacuum at -0.05MPa for 5 hours. Then, add modified liquid phenolic resin PFX003 to submerge the baking sagger, then introduce nitrogen gas to pressurize it to 4.5MPa, and then impregnate it at a temperature of 190°C for 5 hours. After that, take it out and drain it to obtain an impregnated sagger. Step S7: Place the first dipped sagger in a high-temperature vacuum furnace and sinter it at 1150℃ for 78 hours to obtain the second dipped sagger. Step S8: Place the double-baked crucible in a high-temperature pressure vessel, preheat it to 235°C, and then maintain it under vacuum at -0.09MPa for 2.5 hours. Then, add modified liquid phenolic resin PFX003 to submerge the double-baked crucible, then introduce nitrogen gas to pressurize it to 7MPa, and then impregnate it at 235°C for 5 hours. After that, take it out and drain it to obtain the double-impregnated crucible. Step S9: Place the double-dipping sagger in a high-temperature vacuum furnace and sinter it at 1350℃ for 54 hours to obtain a high-density, low-porosity graphite sagger.
[0028] Example 3: This embodiment describes a method for preparing a high-density, low-porosity graphite sagger based on a two-dip, three-baking process, comprising the following steps: Step S1: Add 0.5 mol phenol, 6.5 mL of 28% ammonia solution and 70 g of 38% formaldehyde solution to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection. Stir and react for 30 min at 25℃ and 400 r / min. Then raise the temperature to 75℃ and continue stirring for 3 h. Then dehydrate under reduced pressure at -0.08 MPa for 40 min. Add 0.08 mol boric acid and raise the temperature to 100℃ and continue stirring for 2 h. Then dehydrate under reduced pressure at -0.08 MPa for 40 min. Then add 0.05 mol methyltrimethoxysilane and continue stirring for 50 min. After the reaction is complete, cool the reaction product to room temperature and then place it in a vacuum drying oven and dry at 90℃ for 3 h to obtain heat-resistant phenolic resin. Step S2: Weigh out 75 parts by weight of graphite powder, 6 parts by weight of graphene, 6 parts by weight of heat-resistant phenolic resin, 0.5 parts by weight of zirconium oxychloride, 1.2 parts by weight of alumina, 3 parts by weight of yttrium oxide, 0.5 parts by weight of silane coupling agent KH-560, 3 parts by weight of deionized water, and 10 parts by weight of ethanol for later use; the graphite powder is Naio Nano NO-E-002-3 graphite powder; the graphene is Zhongke Leiming high-purity graphene; the alumina is α-Al2O3 with an average particle size of 30 nm; and the yttrium oxide has an average particle size of 50 nm. Step S3: Mix heat-resistant phenolic resin, zirconium oxychloride, silane coupling agent KH-560, deionized water and ethanol evenly to obtain a binder; Step S4: Mix graphite powder, graphene, alumina, yttrium oxide and binder evenly, then pour into a mold and press for 2 hours under a pressure of 10 MPa, then press for 60 minutes under a pressure of 25 MPa, and then press for 2 minutes under a pressure of 50 MPa to obtain a sagger green. Step S5: Place the sagger green in a high-temperature vacuum furnace and sinter it at 1000℃ for 92 hours to obtain a baked sagger. Step S6: Place a baking sagger in a high-temperature pressure vessel, preheat it to 200°C, and then maintain it under vacuum at -0.05MPa for 6 hours. Then, add modified liquid phenolic resin PFX003 to submerge the baking sagger, then introduce nitrogen gas to pressurize it to 5MPa, and then impregnate it at 200°C for 6 hours. After that, take it out and drain it to obtain an impregnated sagger. Step S7: Place the first dipped sagger in a high-temperature vacuum furnace and sinter it at 1200℃ for 84 hours to obtain the second dipped sagger. Step S8: Place the double-baked crucible in a high-temperature pressure vessel, preheat it to 250°C, and then maintain it under vacuum at -0.09MPa for 3 hours. Then, add modified liquid phenolic resin PFX003 to submerge the double-baked crucible, then introduce nitrogen gas to pressurize it to 8MPa, and then impregnate it at 250°C for 6 hours. After that, take it out and drain it to obtain the double-impregnated crucible. Step S9: Place the double-dipping sagger in a high-temperature vacuum furnace and sinter it at 1400℃ for 60 hours to obtain a high-density, low-porosity graphite sagger.
[0029] Comparative Example 1: This comparative example illustrates a method for preparing a high-density, low-porosity graphite sagger based on a two-dip, three-baking process, comprising the following steps: Step S1: Add 0.5 mol phenol, 6.5 mL of 28% ammonia solution and 70 g of 38% formaldehyde solution to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 25°C and 400 r / min for 30 min. Then raise the temperature to 75°C and continue stirring for 3 h. After that, raise the temperature to 100°C and continue stirring for 2 h. After the reaction is completed, cool the reaction product to room temperature and then place it in a vacuum drying oven and dry at 90°C for 3 h to obtain phenolic resin. Step S2: Weigh out 75 parts by weight of graphite powder, 6 parts by weight of graphene, 6 parts by weight of phenolic resin, 0.5 parts by weight of zirconium oxychloride, 1.2 parts by weight of alumina, 3 parts by weight of yttrium oxide, 0.5 parts by weight of silane coupling agent KH-560, 3 parts by weight of deionized water, and 10 parts by weight of ethanol, and set aside. The graphite powder is Naio Nano NO-E-002-3 graphite powder; the graphene is Zhongke Leiming high-purity graphene; the alumina is α-Al2O3 with an average particle size of 30 nm; and the yttrium oxide has an average particle size of 50 nm. Step S3: Mix phenolic resin, zirconium oxychloride, silane coupling agent KH-560, deionized water and ethanol evenly to obtain a binder; Step S4: Mix graphite powder, graphene, alumina, yttrium oxide and binder evenly, then pour into a mold and press for 2 hours under a pressure of 10 MPa, then press for 60 minutes under a pressure of 25 MPa, and then press for 2 minutes under a pressure of 50 MPa to obtain a sagger green. Step S5: Place the green sagger in a high-temperature vacuum furnace and sinter it at 1000℃ for 8 hours to obtain a high-density, low-porosity graphite sagger.
[0030] Comparative Example 2: This comparative example illustrates a method for preparing a high-density, low-porosity graphite sagger based on a two-dip, three-baking process, comprising the following steps: Step S1: Add 0.5 mol phenol, 6.5 mL of 28% ammonia solution and 70 g of 38% formaldehyde solution to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection and stir at 25°C and 400 r / min for 30 min. Then raise the temperature to 75°C and continue stirring for 3 h. After that, raise the temperature to 100°C and continue stirring for 2 h. After the reaction is completed, cool the reaction product to room temperature and then place it in a vacuum drying oven and dry at 90°C for 3 h to obtain phenolic resin. Step S2: Weigh out 75 parts by weight of graphite powder, 6 parts by weight of graphene, 6 parts by weight of phenolic resin, 0.5 parts by weight of zirconium oxychloride, 1.2 parts by weight of alumina, 3 parts by weight of yttrium oxide, 0.5 parts by weight of silane coupling agent KH-560, 3 parts by weight of deionized water, and 10 parts by weight of ethanol, and set aside. The graphite powder is Naio Nano NO-E-002-3 graphite powder; the graphene is Zhongke Leiming high-purity graphene; the alumina is α-Al2O3 with an average particle size of 30 nm; and the yttrium oxide has an average particle size of 50 nm. Step S3: Mix phenolic resin, zirconium oxychloride, silane coupling agent KH-560, deionized water and ethanol evenly to obtain a binder; Step S4: Mix graphite powder, graphene, alumina, yttrium oxide and binder evenly, then pour into a mold and press for 2 hours under a pressure of 10 MPa, then press for 60 minutes under a pressure of 25 MPa, and then press for 2 minutes under a pressure of 50 MPa to obtain a sagger green. Step S5: Place the sagger green in a high-temperature vacuum furnace and sinter it at 1000℃ for 92 hours to obtain a baked sagger. Step S6: Place a baking sagger in a high-temperature pressure vessel, preheat it to 200°C, and then maintain it under vacuum at -0.05MPa for 6 hours. Then, add modified liquid phenolic resin PFX003 to submerge the baking sagger, then introduce nitrogen gas to pressurize it to 5MPa, and then impregnate it at 200°C for 6 hours. After that, take it out and drain it to obtain an impregnated sagger. Step S7: Place the first dipped sagger in a high-temperature vacuum furnace and sinter it at 1200℃ for 84 hours to obtain the second dipped sagger. Step S8: Place the double-baked crucible in a high-temperature pressure vessel, preheat it to 250°C, and then maintain it under vacuum at -0.09MPa for 3 hours. Then, add modified liquid phenolic resin PFX003 to submerge the double-baked crucible, then introduce nitrogen gas to pressurize it to 8MPa, and then impregnate it at 250°C for 6 hours. After that, take it out and drain it to obtain the double-impregnated crucible. Step S9: Place the double-dipping sagger in a high-temperature vacuum furnace and sinter it at 1400℃ for 60 hours to obtain a high-density, low-porosity graphite sagger.
[0031] Comparative Example 3: This comparative example illustrates a method for preparing a high-density, low-porosity graphite sagger based on a two-dip, three-baking process, comprising the following steps: Step S1: Add 0.5 mol phenol, 6.5 mL of 28% ammonia solution and 70 g of 38% formaldehyde solution to a three-necked flask equipped with a stirrer, thermometer, reflux condenser and gas delivery tube. Purge with nitrogen for protection. Stir and react for 30 min at 25℃ and 400 r / min. Then raise the temperature to 75℃ and continue stirring for 3 h. Then dehydrate under reduced pressure at -0.08 MPa for 40 min. Add 0.08 mol boric acid and raise the temperature to 100℃ and continue stirring for 2 h. Then dehydrate under reduced pressure at -0.08 MPa for 40 min. Then add 0.05 mol methyltrimethoxysilane and continue stirring for 50 min. After the reaction is complete, cool the reaction product to room temperature and then place it in a vacuum drying oven and dry at 90℃ for 3 h to obtain heat-resistant phenolic resin. Step S2: Weigh out 75 parts by weight of graphite powder, 6 parts by weight of graphene, 6 parts by weight of heat-resistant phenolic resin, 0.5 parts by weight of zirconium oxychloride, 1.2 parts by weight of alumina, 3 parts by weight of yttrium oxide, 0.5 parts by weight of silane coupling agent KH-560, 3 parts by weight of deionized water, and 10 parts by weight of ethanol for later use; the graphite powder is Naio Nano NO-E-002-3 graphite powder; the graphene is Zhongke Leiming high-purity graphene; the alumina is α-Al2O3 with an average particle size of 30 nm; and the yttrium oxide has an average particle size of 50 nm. Step S3: Mix heat-resistant phenolic resin, zirconium oxychloride, silane coupling agent KH-560, deionized water and ethanol evenly to obtain a binder; Step S4: Mix graphite powder, graphene, alumina, yttrium oxide and binder evenly, then pour into a mold and press for 2 hours under a pressure of 10 MPa, then press for 60 minutes under a pressure of 25 MPa, and then press for 2 minutes under a pressure of 50 MPa to obtain a sagger green. Step S5: Place the green sagger in a high-temperature vacuum furnace and sinter it at 1000℃ for 8 hours to obtain a high-density, low-porosity graphite sagger.
[0032] The surface of the high-density, low-porosity graphite sagger of Example 3 was subjected to SEM testing, such as... Figure 1 As shown; the interior of the high-density, low-porosity graphite sagger of Example 3 was subjected to SEM testing, as shown... Figure 2 As shown; the surface of the high-density, low-porosity graphite sagger of Comparative Example 1 was subjected to SEM testing, as shown... Figure 3 As shown; the interior of the high-density, low-porosity graphite sagger of Comparative Example 1 was subjected to SEM testing, as shown... Figure 4 As shown.
[0033] according to Figure 3, Figure 4 Obvious pores, cracks, and loose structures can be observed, especially Figure 4 The graphite sagger shows large cavities and irregular intergranular gaps inside, indicating low density and weak internal bonding; according to Figure 1 , Figure 2 respectively with Figure 3 , Figure 4 In comparison, it can be observed that its porosity, cracks, and loose structure are significantly reduced and disappear, especially Figure 2 The graphite sagger shows that the bonding between particles inside the sagger is stronger, the porosity is significantly reduced, and the overall structure is more uniform and dense.
[0034] Performance testing The performance of the high-density, low-porosity graphite saggers of Examples 1-3 and Comparative Examples 1-3 was tested, and the test results are shown in the table below:
[0035] Referring to the data in the table above, and based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that using heat-resistant phenolic resin as a binder and modified liquid phenolic resin as an impregnating agent, and employing a two-dip three-baking process can significantly improve the density and flexural strength of graphite saggers, and significantly reduce the open porosity of graphite saggers.
[0036] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0037] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.
Claims
1. A high-density, low-porosity graphite sagger prepared by two-dip and three-baking processes, characterized in that, Includes the following components by weight: The composition includes 70-75 parts graphite powder, 2-6 parts graphene, 3-6 parts heat-resistant phenolic resin, 0.3-0.5 parts zirconium oxychloride, 0.8-1.2 parts alumina, 1-3 parts yttrium oxide, 0.3-0.5 parts silane coupling agent, 1-3 parts deionized water, and 8-10 parts ethanol. The heat-resistant phenolic resin is prepared by the following steps: Phenol, ammonia solution, and formaldehyde solution were added to a three-necked flask equipped with a stirrer, thermometer, reflux condenser, and gas delivery tube. Nitrogen gas was introduced for protection, and the mixture was stirred for 20-30 minutes at a temperature of 20-25℃ and a stirring rate of 300-400 r / min. The temperature was then raised to 70-75℃ and the stirring was continued for 2-3 hours. The mixture was then dehydrated under reduced pressure at a vacuum of -0.08 MPa for 30-40 minutes. Boric acid was then added, and the temperature was raised to 98-100℃ and the stirring was continued for 1-2 hours. The mixture was then dehydrated under reduced pressure at a vacuum of -0.08 MPa for 30-40 minutes. Methyltrimethoxysilane was then added and the mixture was stirred for 30-50 minutes. After the reaction was completed, the product was cooled to room temperature and then placed in a vacuum drying oven at a temperature of 80-90℃ for 2-3 hours to obtain heat-resistant phenolic resin.
2. The high-density, low-porosity graphite sagger prepared based on two-dip and three-baking processes according to claim 1, characterized in that, The ratio of phenol, ammonia solution, formaldehyde solution, boric acid, and methyltrimethoxysilane is 0.5 mol: 6-6.5 mL: 65-70 g: 0.06-0.08 mol: 0.03-0.05 mol.
3. The high-density, low-porosity graphite sagger prepared based on two-dip and three-baking processes according to claim 1, characterized in that, The ammonia solution has a mass fraction of 27-28%; the formaldehyde solution has a mass fraction of 37-38%.
4. A high-density, low-porosity graphite sagger prepared based on a two-dip, three-baking process according to claim 1, characterized in that, The high-density, low-porosity graphite sagger based on two-dip-three-baking preparation is prepared by the following steps: Step 1: Weigh out 70-75 parts graphite powder, 2-6 parts graphene, 3-6 parts heat-resistant phenolic resin, 0.3-0.5 parts zirconium oxychloride, 0.8-1.2 parts alumina, 1-3 parts yttrium oxide, 0.3-0.5 parts silane coupling agent, 1-3 parts deionized water, and 8-10 parts ethanol according to the following proportions by weight, and set aside. Step 2: Mix the heat-resistant phenolic resin, zirconium oxychloride, silane coupling agent, deionized water and ethanol evenly to obtain the binder; Step 3: Mix graphite powder, graphene, alumina, yttrium oxide and binder evenly, then pour into a mold and press for 1-2 hours under a pressure of 8-10 MPa, then press for 40-60 minutes under a pressure of 20-25 MPa, and then press for 1-2 minutes under a pressure of 40-50 MPa to obtain the sagger green blank. Step 4: The green sagger blank is subjected to a two-dip and three-baking process to obtain a high-density, low-porosity graphite sagger.
5. A high-density, low-porosity graphite sagger prepared based on a two-dip, three-baking process according to claim 4, characterized in that, The alumina is α-Al2O3 with an average particle size of 30 nm.
6. A high-density, low-porosity graphite sagger prepared based on a two-dip, three-baking process according to claim 4, characterized in that, The average particle size of the yttrium oxide is 50 nm.
7. A high-density, low-porosity graphite sagger prepared based on a two-dip, three-baking process according to claim 4, characterized in that, The two-dip, three-baking process includes the following steps: Step A1: Place the sagger blank in a high-temperature vacuum furnace for a first sintering to obtain a baked sagger; Step A2: Dip a baking sagger once to obtain a dipped sagger; Step A3: Place the first dipped sagger in a high-temperature vacuum furnace for secondary sintering to obtain a second-baked sagger; Step A4: Dip the two-baking saggers a second time to obtain two-dipping saggers; Step A5: Place the double-dipping sagger in a high-temperature vacuum furnace for three sintering processes to obtain a high-density, low-porosity graphite sagger.
8. A high-density, low-porosity graphite sagger prepared based on a two-dip, three-baking process according to claim 7, characterized in that, The conditions for the first sintering in step A1 are: sintering at a temperature of 900-1000℃ for 84-92 hours; the conditions for the second sintering in step A3 are: sintering at a temperature of 1100-1200℃ for 72-84 hours; and the conditions for the third sintering in step A5 are: sintering at a temperature of 1300-1400℃ for 48-60 hours.
9. A high-density, low-porosity graphite sagger prepared based on two-dip and three-baking processes according to claim 7, characterized in that, The specific process of one immersion in step A2 is as follows: A baking sagger is placed in a high-temperature pressure vessel, preheated to 180-200℃, and then vacuumed to -0.05MPa for 4-6 hours. Modified liquid phenolic resin is then added to submerge the baking sagger, followed by nitrogen gas to pressurize to 4-5MPa. The sagger is then immersed at 180-200℃ for 4-6 hours, and then removed and drained to obtain an immersed sagger.
10. A high-density, low-porosity graphite sagger prepared based on a two-dip, three-baking process according to claim 7, characterized in that, The specific process of the secondary impregnation in step A4 is as follows: The double-baked crucible is placed in a high-temperature pressure vessel, preheated to 220-250℃, and then vacuumed to -0.09MPa for 2-3 hours. After that, modified liquid phenolic resin is added to submerge the double-baked crucible, and then nitrogen gas is introduced to pressurize it to 6-8MPa. After that, it is immersed at a temperature of 220-250℃ for 4-6 hours. After that, it is taken out and drained to obtain the double-immersion crucible.